Motivational Interviewing as an Intervention to Improve Achievement Motivation in Students Experiencing Bullying - Bambang Dibyo Wiyono; Riska Dwi Kurni Sari; Mochamad Nursalim; Najlatun Naqiyah; Wiryo Nuryono; Bakhrudin All Habsy; Muhamad Afifuddin Ghozali; Akmal Nasri Kamal (Universitas Negeri Padang, 2026)
Bullying in schools continues to affect victims in various ways. One significant impact is the decline in their academic performance and achievement motivation. This study aimed to evaluate the effectiveness of motivational interviewing techniques in enhancing achievement motivation among victims of bullying. It employed a true experimental design with a pre-test and post-test control group. Data were gathered using an achievement motivation scale developed specifically for victims of bullying. Participants were selected based on their responses, specifically those with low achievement motivation. Since the data were not normally distributed, the Mann-Whitney test was used for analysis. An N-gain test assessed the technique's effectiveness. Results from the Mann-Whitney test showed a significant difference (p = 0.009) in score distributions between the experimental and control groups after intervention. The experimental group, which received motivational interviewing, achieved an average N-gain score of 58.05%, indicating it was quite effective compared to the control group that received routine counselling. In summary, motivational interviewing techniques have demonstrated considerable effectiveness in increasing achievement motivation among victims of bullying.